2018
DOI: 10.1016/j.rboe.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

488 hand surgeries with local anesthesia with epinephrine, without a tourniquet, without sedation, and without an anesthesiologist

Abstract: ObjectivesEvaluate the incidence of digital infarction and tissue necrosis using local anesthesia with 1% lidocaine and 1:100,000 epinephrine in wrist, hand, and fingers surgeries, without a tourniquet, without sedation, and without an anesthesiologist.MethodsPatients with wrist, hand, and fingers disorders prospectively underwent surgery under local anesthesia with 1% lidocaine and 1:100,000 epinephrine. The primary outcomes evaluated were the presence of digital infarction and tissue loss due to necrosis. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…Golyakhovks e Franzel também destacam a técnica para extração do fio, enfatizando a remoção cuidadosa para evitar sangramentos, que pode ser gerenciado ambulatorialmente. Sardenberg et al (2018) reportaram alta satisfação em cirurgias da mão realizadas com anestesia local contendo epinefrina, sem sedação ou assistência anestésica, reforçando a segurança da anestesia local mesmo em mãos de cirurgiões menos experientes.…”
Section: Resultsunclassified
“…Golyakhovks e Franzel também destacam a técnica para extração do fio, enfatizando a remoção cuidadosa para evitar sangramentos, que pode ser gerenciado ambulatorialmente. Sardenberg et al (2018) reportaram alta satisfação em cirurgias da mão realizadas com anestesia local contendo epinefrina, sem sedação ou assistência anestésica, reforçando a segurança da anestesia local mesmo em mãos de cirurgiões menos experientes.…”
Section: Resultsunclassified
“…33 Um estudo brasileiro avaliou o uso de anestesia local com lidocaína e epinefrina nas cirurgias do punho, mão e dedos, sem torniquete, sem sedação e sem anestesista, e não relatou nenhuma complicação relacionada à epinefrina. 34 O tratamento cirúrgico do dedo de gatilho tem uma taxa de sucesso relatada de até 97%. 3,22 A cirurgia percutânea apresentou sucesso de 60 a 90% para 43,0% dos respondedores, sendo a complicação mais comum a recidiva do engatilhamento.…”
Section: Discussionunclassified
“…Clinical studies initiated at Cipto Mangunkusumo Hospital, Jakarta, demonstrated advancements, with international research publications supporting the technique's efficacy. [21][22][23][24][25][26] The presentation also highlighted challenges faced in the global plastic surgery community regarding using epinephrine in certain surgeries, emphasizing the safety measures adopted in Jakarta, where awareness gained through experimental research contributed to clinical success. 27 The surgical innovation of hand surgery without a tourniquet has proven effective, offering advantages in safety, efficiency, and good and excellent patient experience across various hand surgeries.…”
Section: Hand Surgery Without Tourniquetmentioning
confidence: 99%